The impact of myofascial shoulder pain on hopelessness state among women in Turkey - Karalezli, Nazim; Ipek, Ozge; M. Saleh, Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2020)
One of the major complaints of patients for consulting primary healthcare providers is shoulder pain. The most common causes of this problem are subacromial impingement syndrome (SIS). The aim of the current study was to evaluate the hopelessness status of women with myofascial shoulder pain and to compare them with women suffering from traumatic pain. The prospective study design was used in the current study, 60 women were assigned equally to Myofascial group (group M), a group where women complain of shoulder pain, palpable, and tender myofascial trigger points, and 30 women who sustained traumatic shoulder pain in the control group (group T). Beck Hopelessness Scale was used to detect the hopelessness level. Mann Whitney U test was used for statistical analysis. P <0.05 was considered significant. The results showed that the mean was a statistically significant difference between the groups regarding hopelessness state (7.4) for the myofascial group and (3.8) for the traumatic group, P <0.05. Hopelessness status of women with myofascial shoulder pain should be acknowledged because women may need social and psychological support in addition to medical treatment to overcome their complaints.